2014
DOI: 10.5530/jyp.2014.4.6
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study on the anti-microbial effi cacy of ten herbal extracts on primary plaque colonizers

Abstract: Introduction: To assess and compare the anti-microbial effi cacy of ten herbal extracts against primary plaque colonizers. Materials and Methods:The branches of 10 plants with ethno-pharmacological background were collected and healthy leaves separated to prepare the fi ne powder. The extraction procedure was carried out by cold infusion method using ethanol. The working concentration of the extract (100 mg/ml) was prepared by mixing dried leaf extract with dimethyl sulfoxide (DMSO). 0.2% chlorhexidine and DMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…The inoculum was cell suspension prepared from cultures grown on trypticase soy broth adjusted to 1.2 × 10 5 . The positive control was chlorhexidine mouth wash-0.2% [ 8 11 ] and ciprofloxacin 250 mg [ 12 ] and the negative control was methanol.…”
Section: Methodsmentioning
confidence: 99%
“…The inoculum was cell suspension prepared from cultures grown on trypticase soy broth adjusted to 1.2 × 10 5 . The positive control was chlorhexidine mouth wash-0.2% [ 8 11 ] and ciprofloxacin 250 mg [ 12 ] and the negative control was methanol.…”
Section: Methodsmentioning
confidence: 99%
“…An acetone extract of the leaves of an M. indica variety grown in Pakistan exerted a strong inhibition of growth of multidrug resistant S. typhi [ 216 ]. Antibacterial effects of several mango leaf extracts grown in India have been proven in several bacterial species by Bharti, 2013 ( M. indica variety collected from Rewa district, Madhya Pradesh) [ 217 ], Chandrashekar et al 2014 (mango variety collected from Bhopal, Madhya Pradesh) [ 218 ], Madduluri et al, 2013 (collected from Andhra Pradesh) [ 219 ], and Sharwat et al, 2013 (collected from Meerut region) [ 220 ]. Bhati, 2013 found that hexane and hexane/ethyl acetate extracts of leaves exert promising antibacterial effects against Mycobacterium tuberculosis , Enterobacter aerogenes , and S. pyogenes .…”
Section: Pharmacological Properties Of M Indicamentioning
confidence: 99%
“…Bharti [28] refiere que los extractos de hexano y hexano / acetato de etilo de las hojas de M. indica (India) ejerce prometedores efectos antibacterianos contra Mycobacterium tuberculosis, Enterobacter aerogenes y Streptococcus pyogenes. Chandrashekaret et al [29] informaron que el extracto etanólico de las hojas de M. indica L., puede inhibir el crecimiento de Streptococcus mutans.…”
Section: Resultados Y Discusiónunclassified